Impact of US Involvement & Withdrawal from Afghanistan on Afghan Refugees in Pakistan - Ayesha Amir; Dr. Syed Khawaja Alqama (Indus Journal of Social Sciences, 2025)
This article analyses the socio-economic and security issues presented by Afghan refugees in Pakistan, especially in the aftermath of U.S. engagement and eventual withdrawal from Afghanistan. The research examines the historical context of Afghan migration to Pakistan, emphasising the effects of the Afghan Jihad and the War on Terror, which resulted in the arrival of millions of refugees. The article examines the pressure on Pakistan’s resources, infrastructure, and security, emphasising the increase in militancy and social unrest in regions accommodating refugees. The research used an exploratory design to assess the broader implications of this issue for Pakistan and Afghanistan. The results indicate that return, conducted under secure and voluntary circumstances, is the most feasible approach to mitigate Pakistan’s burden while facilitating the return of refugees to a stable Afghanistan. The article advocates for collaboration among the Afghan government, Pakistan, and the international community to establish favourable conditions for the restoration process, emphasising infrastructure, security, and economic prospects. The resolution of the refugee problem is deemed essential for promoting peace, stability, and development in the region.